âÃDAH SEBAGAI SUMBER HUKUM ISLAM DAN PRAKTEKNYA DALAM PENYELESAIAN SENGKETA TANAH - Maladi, Yanis (LP2M IAIN Mataram, 2010)
One of the main purposes of law is to uphold truth and justice. Laws is not merely seen as a compilation of regulations but reflection of societyâs ideas of moral values and ethics. The basic strength of law lies on its ability to disseminate ideas, and visions based on peopleâs experiences from time to time. The Qurâan, as a source of Islamic law, explicitly instructs people to adopt and apply virtues and good ethics such as assigning trustworthy to those who can bear it and to consult with each other to reach a consensus and resolve disputes. This study is aimed at giving understanding toward the society about advantages of Islamic values and âÃ¢dah as a main source for settling land disputes. The goal of these values is to gain truth, virtue and justice. The study found some model of land dispute resolutions. However, the most popular method taken by people is resolution out of courts (non-litigation) where religious or local figures often acted as the mediator of the conflict.